Maternal superobesity and perinatal outcomes - Marshall, Nicole E. (2012)
OBJECTIVE: The purpose of this study was to determine the effect of maternal superobesity (body mass index [BMI], ≥50 kg/m(2)) compared with morbid obesity (BMI, 40–49.9 kg/m(2)) or obesity (BMI, 30–39.9 kg/m(2)) on perinatal outcomes. STUDY DESIGN: We conducted a retrospective cohort study of birth records that were linked to hospital discharge data for all liveborn singleton term infants who were born to obese Missouri residents from 2000–2006. We excluded major congenital anomalies and women with diabetes mellitus or chronic hypertension. RESULTS: There were 64,272 births that met the study criteria, which included 1185 superobese mothers (1.8%). Superobese women were significantly more likely than obese women to have preeclampsia (adjusted relative risk [aRR], 1.7; 95% confidence interval [CI], 1.4 –2.1), macrosomia (aRR, 1.8; 95% CI, 1.3–2.5), and cesarean delivery (aRR, 1.8; 95% CI, 1.5–2.1). Almost one-half of all superobese women (49.1%) delivered by cesarean section, and 33.8% of superobese nulliparous women underwent scheduled primary cesarean delivery. CONCLUSION: Women with a BMI of ≥50 kg/m(2) are at significantly increased risk for perinatal complications compared with obese women with a lower BMI.